Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0092155
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Fingers Function Cooperatively with KRAB Domain for Nuclear Localization of KRAB-Containing Zinc Finger Proteins

Abstract: Multiple nuclear localization domains have been identified in nuclear proteins, and they finely control nuclear import and functions of those proteins. ZNF268 is a typical KRAB-containing zinc finger protein (KRAB-ZFP), and previous studies have shown that the KRAB domain reinforces nuclear localization of KRAB-ZFPs by interacting with KAP1. In this study, we find that some of 24 zinc fingers of ZNF268 also possess nuclear localization activity. Results of mutagenesis studies suggest that KRAB and zinc fingers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…Upon depletion of ZNF268a, SeV-induced NF-κB promoter activation was severely dampened ( Figure 3A). Our group s earlier work revealed predominant nuclear localization of ZNF268a [37,38]; however, the current immunofluorescence analysis using exogenously flag-tagged ZNF268a revealed a relatively small but clear cytoplasmic distribution of ZNF268a ( Figure 3B), which raised the possibility that ZNF268a might regulate NF-κB dependent cytokine production in the cytoplasm by affecting NF-κB signal transduction. Indeed, phosphorylation of NF-κB subunit p65, a hallmark of NF-κB activation, was severely impaired in ZNF268a-knockout cells following viral infection, in contrast to that in their wild-type counterparts ( Figure 3C).…”
Section: Znf268a Influenced Cytokine Expression By Regulating the Nf-contrasting
confidence: 64%
See 1 more Smart Citation
“…Upon depletion of ZNF268a, SeV-induced NF-κB promoter activation was severely dampened ( Figure 3A). Our group s earlier work revealed predominant nuclear localization of ZNF268a [37,38]; however, the current immunofluorescence analysis using exogenously flag-tagged ZNF268a revealed a relatively small but clear cytoplasmic distribution of ZNF268a ( Figure 3B), which raised the possibility that ZNF268a might regulate NF-κB dependent cytokine production in the cytoplasm by affecting NF-κB signal transduction. Indeed, phosphorylation of NF-κB subunit p65, a hallmark of NF-κB activation, was severely impaired in ZNF268a-knockout cells following viral infection, in contrast to that in their wild-type counterparts ( Figure 3C).…”
Section: Znf268a Influenced Cytokine Expression By Regulating the Nf-contrasting
confidence: 64%
“…In agreement with their roles as transcriptional regulators, KRAB-ZFPs are mainly located in the cell nucleus. Our previous work showed that ZNF268a is mainly located in the cell nucleus [37,38]. Despite that, we found that NF-κB signal transduction, which occurs in the cytoplasm, is inhibited in ZNF268a-deficient cells.…”
Section: Discussionmentioning
confidence: 53%
“…Zinc finger protein is one of the most important transcription factors and plays an important role in regulating gene expression35. More recently, ZNF300 and its novel splice variant were observed to be highly expressed in human testis, suggesting their essential roles in prolificacy36.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that both of the KRAB domain and zinc fingers are necessary for the nuclear localization of KRAB-ZFPs [ 11 ]. To determine sub-domains within ZFP809 responsible for its nuclear localization, we subjected 293FT cells expressing the intact or one of the truncated/mutated ZFP809 proteins to immunostaining using anti-FLAG and anti-fibrillarin antibodies, of which the latter is used to stain nucleoli.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have reported the involvement of KRAB-ZFPs in various cellular processes such as metabolism, immunity, apoptosis, cancer, development and differentiation [ 1 , 4 , 7 10 ], cellular functions and subcellular localization of many KRAB-ZFPs remain unknown. A recent study has shown that ZNF268, a member of human KRAB-ZFPs, is localized in the nucleus and not nucleoli through cooperative functions of zinc finger motifs and the KRAB domain [ 11 ].…”
Section: Introductionmentioning
confidence: 99%